Chapter Periodontal Considerations in Adult Orthodontic Patients - Roberto Grassi, Felice (InTechOpen, 2017)
The relationship between periodontology and orthodontics consists of a highly complex, bidirectional and close interaction that is nowadays characterized by controversial scientific opinions and clinical approaches. The relevant increasing number of adult orthodontic patients which in most cases present already-compromised periodontal tissues has markedly highlighted the potential of orthodontic treatment in enhancing or deteriorating periodontal health and also the outmost relevance of peculiar periodontal planning prior and during orthodontic treatment. Since the progress in adult orthodontics trend is rapid, there is also an increasing need for evidence-based protocols that might guide clinicians through a comprehensive, interdisciplinary and successful treatment. This chapter has been compiled with the aim of providing orthodontists, periodontists and general practitioners with sound evidence-based protocols and valid clinical approaches that have proven to be successful for numerous patients over long follow-ups. It is structured following the steps for a correct therapy management, starting from comprehensive examination and diagnosis to before and during orthodontic treatment considerations, and finally analysing the present state of new adult orthodontic technologies.